Examining Preoperative MRI for Medial Meniscal Ramp Lesions in Patients Surgically Treated for Acute Grade 3 Combined Posterolateral Corner Knee Injury. Issue 2 (3rd February 2023) - Moran, Jay; Jimenez, Andrew E.; Katz, Lee D.; Wang, Annie; McLaughlin, William M.; Gillinov, Stephen M.; Patel, Rohan R.; Kunze, Kyle N.; Hewett, Timothy E.; Alaia, Michael J.; LaPrade, Robert F.; Medvecky, Michael J.
Background: While medial meniscocapsular tears (ramp lesions) are commonly associated with isolated anterior cruciate ligament injuries, there are limited descriptions of these meniscal injuries in multiligament knee injuries (MLKIs). Purpose: To (1) retrospectively evaluate preoperative magnetic resonance imaging (MRI) scans for the presence of ramp lesions in patients surgically treated for acute grade 3 combined posterolateral corner (PLC) knee injuries and (2) determine if a preoperative posteromedial tibial plateau (PMTP) bone bruise is associated with the presence of preoperative ramp lesions on MRI in these same patients. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Data on consecutive patients at a level 1 trauma center with MLKIs between 2001 and 2021 were retrospectively reviewed. Only patients with acute grade 3 combined PLC injuries who received an MRI scan within 30 days of injury were assessed. Two musculoskeletal radiologists retrospectively reviewed each patient's preoperative MRI for evidence of ramp lesions and bone bruises. Intraclass correlation coefficients (ICCs) were used to calculate reliability among the reviewers. Multivariate analysis was used to evaluate the relationship between PMTP bruising and the presence of a ramp lesion on MRI. Results: A total of 68 patients (79.4% male; mean age, 33.8 ± 13.7 years) with an acute grade 3 combined PLC injury were included in the study. On MRI, the ICCs for detection of ramp lesions and PMTP bone bruising were 0.921 and 0.938, respectively. Medial meniscal ramp lesions were diagnosed in 18 of 68 (26.5%) patients. Eleven of 18 (61.1%) patients with ramp lesions also showed evidence of PMTP bruising, while 13 of 50 (26.0%) patients without ramp lesions had PMTP bruising ( P = .008). When controlling for age and sex, PTMP bruising was significantly associated with the presence of a ramp lesion in combined PLC injuries (odds ratio, 4.62; P = .012). Conclusion: Preoperative medial meniscal ramp lesions were diagnosed on MRI in 26.5% of patients with acute grade 3 combined PLC injuries. PMTP bone bruising was significantly associated with the presence of a ramp lesion on MRI. These findings reinforce the need to assess for potential ramp lesions at the time of multiligament reconstruction.